Sulfur sources in protein supplements for ruminants - Silva, Cássio José da (2014)
The present study evaluates the efficiency of different sulfur sources for ruminant nutrition. The fiber digestibility and the amino acid profile were analyzed in the duodenal digesta of crossbred steers fed Brachiaria dictyoneurahay. The sources utilized were elemental sulfur (ES70S), elemental sulfur (ES98S); calcium sulfate in hydrated (HCS), CaSO4.2H2O, and anhydrous (ACS), CaSO4, forms; and ammonium sulfate (AS), (NH4)2SO4, keeping a nitrogen:sulfur ratio of 11:1. The iso-protein supplements had 50% of protein in the total dry matter (DM). Five Holstein × Zebu steers, which were fistulated in the rumen and abomasum, were distributed in a 5 × 5 Latin square. The different sulfur sources in the supplement did not affect any of the evaluated nutritional factors, such as intake of hay dry matter and protein supplement, crude protein (CP), neutral detergent fiber corrected for ash and protein (NDFap), organic matter (OM), non-fibrous carbohydrate (NFC), ether extract (EE), total digestible nutrients (TDN), NDFap and CP digestibility coefficients, ruminal pH, and ruminal ammonia concentration. The concentrations of amino acids available in the abomasal digesta did not differ significantly in the tested diets. The sulfur sources evaluated in the present study are suitable as supplement for cattle, and their employment may be important to avoid environmental contaminations.